The teacher’s social value and its impact in the teacher identity education: an analytic study (Olhar de Professor, 2022)
The current study aims to present primary school’s teachers’ perception relating to their teacher identity, as well as how the surrounding agents understand this professional, attributing value or not. The methodological framework is based in considerations made by Charlot (2000); Pimenta (1999), Nóvoa (1997) e Tardif (2002) The Such analysis was reinforced through data collection, using interviews with teachers and questionnaires answered by families. Such data constituted the analyses’ corpus through a qualitative approach. The discussion also refers to the way in which many teachers believe that teacher training goes through the vocational sphere.  The article is divided into three sections, which address: (1) the teaching identity constitution, (2) the ways teachers can be valued, emphasizing social valuations and (3) the analysis of the data collected. The results from the research point that The social devaluation of the teacher comes from a historical context that considers the teaching profession related to vocation, which interferes in the construction of the identity of this professional.
Keywords: Teacher training. Teacher identity. Teacher valuation